Richness, relative abundance and activity of medium and large mammals of a reserve under restoration in Costa Rica (UNED Research Journal, 2022)
ABSTRACT. “Richness, relative abundance and activity of medium and large mammals of a reserve under restoration in Costa Rica”. Introduction: Private protected areas are a valuable complement to national systems of protected areas. The Sierra Zapote Reserve in Abangares, Costa Rica, established in 2000, protects 70 ha of advanced secondary forest, regenerating secondary forest and primary riparian forest. It is expected to favor faunal communities, like medium and large mammals, which are among the species most threatened by habitat loss and fragmentation; nevertheless; there is a lack of recent faunal assessments at Sierra Zapote. Objective: To assess the richness, relative abundance and activity patterns of these mammals in the reserve. Methods: From May 2020 to July 2021, we kept five camera-traps at strategic sites and programmed them to be active 24 hours a day (0,3 seconds between shots). We checked the cameras every one or two months and also extracted temperature and moon phase data. Results: We obtained 758 independent records of mammals with a 2 135-day photo-trapping effort. The most abundant species were Nasua narica (relative abundance index RAI = 14,6, N= 312) and Didelphis marsupialis (RAI = 6,1, N= 130). The least abundant were Herpailurus yagouaroundi and Procyon lotor (RAI = 0,05, N= 1). Most species are nocturnal and only the peccary (Pecari tajacu), the coati (Nasua narica) and the agouti (Dasyprocta punctata) have mostly diurnal activity. The puma (Puma concolor) occurs at the reserve. Conclusion: The activity patterns were as expected; for the reserve size, a richness of 19 species is comparatively high. The presence of the puma, an indicator of good ecosystem health, hints at the importance of the reserve’s restoration process.